PDE3B as a multi-organ therapeutic node in the gut–liver axis of metabolic dysfunction-associated steatohepatitis - Yu Seol Lee; Chang-Yun Jeong; Youn Wook Chung; Yoseob Lee; Da Hyun Lee; Ji Yun Bang; Da Ye Kim; Haram Lee; Soohwan Oh; Jinhyuk Bhin; Ji-Hwan Ryu; June-Yong Lee; et al. (Experimental & Molecular Medicine, 2026)
Abstract Metabolic dysfunction-associated steatohepatitis (MASH) involves pathological crosstalk within the gut–liver axis, in which intestinal barrier dysfunction facilitates the translocation of microbial and dietary products and aggravates hepatic inflammation and fibrosis. Although phosphodiesterase 3B (PDE3B) is known to regulate metabolic and inflammatory processes, its role in gut–liver communication remains unclear. Here, we demonstrate that genetic ablation of PDE3B and pharmacological PDE3 inhibition using cilostamide significantly improve hepatic and intestinal features of MASH in diet-induced mouse models. Specifically, PDE3B loss and pharmacological PDE3 inhibition preserve intestinal barrier integrity by restoring tight junction protein expression and reducing intestinal permeability, accompanied by attenuated hepatic inflammatory and fibrotic responses. Mechanistically, loss of PDE3B suppresses nuclear factor-κB-driven inflammatory signaling through activation of a cAMP-protein kinase A-dependent pathway, as reflected by increased phosphorylation of cAMP response element-binding protein. Notably, ileal PDE3B protein declines earlier than hepatic PDE3B during MASH progression, supporting early intestinal engagement during diet-induced metabolic stress. These findings support PDE3B/PDE3 signaling as a therapeutically tractable multi-organ regulatory node of gut–liver axis pathology in MASH and identify pharmacological PDE3 inhibition as a viable strategy to mitigate hepatic injury while preserving intestinal barrier-associated function.